Legal Protection against Personal Data Breaches in Electronic Media: A Rule of Law Perspective and Global Challenges - Saputera, Muhammad Iqbal; Fitria, Laila Indriyanti (Technium Social Sciences Journal, 2026)
Personal data breaches through electronic media are increasingly frequent, impacting not only national legal systems but also raising international concerns regarding cross-border data security. This article examines the legal protection against electronic data breaches in Indonesia within the framework of the rule of law and democratic principles. Using a normative approach and grounded in the theory of the rule of law and democracy, the study finds that despite the enactment of the Personal Data Protection Law (PDP Law), challenges remain in its implementation and oversight. These challenges demand stronger international cooperation, transnational policy harmonization, and cross-sectoral approaches.